FOREIGNIZATION AND DOMESTICATION OF LEXICONS USED IN THE NOVEL “DID I MENTION I LOVE YOU” TRANSLATED BY DINA BEGUM - Baiq Zuhaerana; Untung Waluyo; Lalu Thohir (Journal of English Education Forum (JEEF), 2021)
This research was aimed at finding Foreignization and Domestication in the novel Did I Mention I love You? It also described the cultural-specific terms of the data found. The data collected from the novel Did I Mention I Love You? and its translation were presented by descriptive qualitative method. The findings reveal that there were several techniques belong to foreignization and so do domestication. Foreignization consisted of literal translation, transliteration, borrowing, and transference while domestication consisted of transposition, omission, addition, and adaptation. It was also found some categories of cultural-specific terms. The result of this research showed that there were 287 data of foreignization and 565 data of domestication. Furthermore, there were 137 data of foreigization and 219 data of domestication categorized in cultural-specific terms classification based on Newmark’s.